2005
DOI: 10.1007/s00018-005-5422-7
|View full text |Cite
|
Sign up to set email alerts
|

A structure-activity study for the inhibition of metalloproteinase-9 activity and gene expression by analogues of gallocatechin-3-gallate

Abstract: Catechins are able to modulate the gelatinolytic activity of matrix metalloproteinase-9 (MMP-9) by reducing its release from macrophages. Gallocatechins decrease MMP-9 secretion by lowering MMP-9 promoter activity and mRNA levels. The effect appears to be dependent on some structural and stereochemical requirements. In this study, the relationship between chemical structure and activity was studied by testing the effect of analogues of (+/-)-gallocatechin-3-gallate (+/-)-GCG, selectively deprived of hydroxyl g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…In accordance with the earlier findings, commitment with the increased production of fibrotic mediators was the up-regulation of SHH signaling upon the administration of TGF-β [9,10,16]. The present study extends the previous work of our group on the positive role of SHH signaling in promoting the synthesis of fibrotic mediators as we reported that aberrant SHH Chen J et al demonstrated that flavanol glycosides exert antioxidant activities and vascular protective potential in diabetic mice via the suppression of the NF-κB signaling pathway [21] whereas Dell'agli M and colleagues showed that catechins, compounds of flavanol derivatives, lowered MMP9 secretion via inhibiting NF-κB activation [26]. Apart from fibrosis and pancreatitis, SHH signaling also plays important roles in some intercalating pathologies such as pancreatic tumorgenesis, metastasis and invasion [27,28].…”
Section: Discussionsupporting
confidence: 72%
“…In accordance with the earlier findings, commitment with the increased production of fibrotic mediators was the up-regulation of SHH signaling upon the administration of TGF-β [9,10,16]. The present study extends the previous work of our group on the positive role of SHH signaling in promoting the synthesis of fibrotic mediators as we reported that aberrant SHH Chen J et al demonstrated that flavanol glycosides exert antioxidant activities and vascular protective potential in diabetic mice via the suppression of the NF-κB signaling pathway [21] whereas Dell'agli M and colleagues showed that catechins, compounds of flavanol derivatives, lowered MMP9 secretion via inhibiting NF-κB activation [26]. Apart from fibrosis and pancreatitis, SHH signaling also plays important roles in some intercalating pathologies such as pancreatic tumorgenesis, metastasis and invasion [27,28].…”
Section: Discussionsupporting
confidence: 72%
“…Furthermore, the 15 synthesized catechins were all racemic mixtures, different from the ones of green tea extract that are present as (−) stereoisomers. The use of racemic mixtures greatly facilitated the synthesis, thus avoiding chiral chromatography or stereoselective reactions, and is supported by previous work describing the lack of stereoselectivity in the biological activity of catechins . On the other hand, in all cases racemic gallocatechin‐3‐gallate (compound 1 ) was compared with natural (−)‐GCG.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that both natural (−)‐GCG and synthetic (±)‐GCG (compound 1 ) exert an inhibitory action similar to (−)‐EGCG, and their K D values are comparable, indicating that these epimeric compounds cannot be distinguished and that the anti‐STAT1 activity lacks stereoselectivity. The present results are in agreement with our previous report that showed the scarce relative importance of stereochemistry on metalloproteinase‐9 protease transcription activation . On the other hand, our data are not in agreement with a paper by Tsuchiya where optical isomers of catechins are characterized by different effects on membrane fluidity .…”
Section: Discussionmentioning
confidence: 99%
“…The gelatinolytic activity of MMP-9 secreted by THP-1 cells was evaluated as previously described [23]. Briefly, cells were exposed to TNF or HZ in the presence of the tested compounds.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, cells were exposed to TNF or HZ in the presence of the tested compounds. Epigallocatechin-3-gallate (EGCg) 20 μM was used as reference inhibitor of MMP-9 expression [23]. Control samples received the vehicle only.…”
Section: Methodsmentioning
confidence: 99%